Anti-Digitalization as a Strategy to Harmonize Human-Nature Relationships in the Baduy Dalam Community - Maharani, Septiana Dwiputri; Dony, Ahmad Rama (Institut Filsafat dan Teknologi Kreatif Ledalero, 2025)
The increasing development of technology has raised concerns among some people regarding its impact on the relationship between humans and nature. This study examines the anti-digitalization attitudes of the Baduy Dalam community as a deliberate effort to maintain harmony between humans and nature. Utilizing a phenomenological approach, this research explores the philosophical foundations of the Baduy Dalam’s resistance to modern technology, focusing on their adherence to traditional ecological practices. The findings of this study indicate that the Baduy Dalam community’s way of life, by rejecting digitalization, offers a unique model for rethinking the role of technology in modern society. This research contributes to a broader philosophical discourse about the relationship between humans, technology, ecology, and indigenous knowledge systems, suggesting that the anti-digitalization practices of the Baduy Dalam serve as a reminder of the importance of maintaining harmony between humans and nature amid rapid technological changes.Keywords: Anti-Digitalization, Human and Nature Harmony, Baduy Dalam Community, Environmental Conservation, Cultural Tradition